Intergovernmental Transfer and Local Own-Source Revenue on Capital Expenditure - Susilo, Susilo; Putri, Risqi Noor Hidayati; Simangunsong, Finka Yolanda; Labiba, Mutiara (Eqien - Jurnal Ekonomi dan Bisnis, 2024)
During the reform era, regional autonomy has been implemented to develop each regency/city effectively and effi-ciently. The central government has delegated authority and given intergovernmental transfers to local governments to regulate and determine the priorities of their regional development. Unfortunately, the effectiveness of the trans-fer by increasing capital expenditure allocation often becomes controversial. In the recent 5 years, the percentage of capital expenditure realization is lower than that of the capital expenditure. In 2018, the average percentage of regional personnel expenditure in Indonesia was around 35.6%, while the capital expenditure was only 19.4% (DJPK, 2018). In 2022, the situation was getting worse because the personnel expenditure was allocated 62.5%, while the capital expenditure was only 15.8% (DJPK, 2022). Although the Minister of Home Affairs Regulation Number 27 of 2013 has stated that each region should allocate its capital expenditure at least 30% from the APBD, but in reality there are still many regions that haven’t complied with this rule. In Riau, until 2021 there have been no regencies/cities that can fulfill the regulation. The purpose of this paper is to analyze the impact of General Alloca-tion Fund (DAU), Special Allocation Fund (DAK), Revenue Sharing Fund (DBH) and Local Own-Source Revenue (PAD) on capital expenditure in regencies/cities of Riau in the period of 2018-2021. The analytical method applys multiple regression analysis based on Pooled Least Square model. The result reveals that capital expenditure is sig-nificantly and positively affected by DAK and PAD. Meanwhile, DBH and DAU have insignificant effect on capital expenditure of Riau in 2018-2021